(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The critical period for weed control is that part of the cropgrowth cycle during which the crop must be kept weed-free to preventunacceptable yield losses. Field studies were conducted for twoconsecutive years, 2004 and 2005, in the Thessaly plain in central Greeceto determine the critical period for weed control in cotton at three nitrogenlevels (50,100, and 150 kg N ha-1 ).Treatments of increasing duration ofweed interference and weed-free period were imposed at biweeklyintervals from 0 to 10 weeks after crop emergence (WAE). Based on anarbitrarily acceptable yield loss level of 5% and 10%, the beginning andend of the critical period were determined by fitting the polynomialregression to relative yield data representing increasing duration of weedinterference and weed-free period. Plant height, shoot and root dryweights and yield of cotton were reduced by prolonged delays in weedremoval at all nitrogen levels in 2004 and 2005. The results showed thatweeds reduced cotton shoot and root dry weights, respectively, by 55%and 38 % at 50 kg N ha-1 , 50% and 42 % at 100 kg N ha-1 and 40% and 46% at 150 kg N ha -1 , when allowed to compete for two weeks. At 10%acceptable yield loss level, the critical period was 8.2 weeks, starting 0.4WAE and ending 8.6 WAE at 50 kg N ha -1 , and was decreased to 7weeks, starting 1 WAE and ending 8 WAE at 100 kg N ha-1 . The criticalperiod decreased to 6.1 weeks, at 150 kg N ha -1 , starting 1.3 WAE andending 7.4 WAE. These findings showed that the supply of nitrogen to thecrop and weeds significantly influenced the crop-weed interferenceduration. This information will be useful for providing weed controlrecommendation to cotton producers.